Dermoscopic features of lupus miliaris disseminatus faciei: Distinct aspects depending on disease stage. Issue 9 (16th June 2020) - Litaiem, Noureddine; Chamli, Amal; Bacha, Takwa; Jones, Meriem; Goucha, Samia; Rammeh, Soumaya; Zeglaoui, Faten
Abstract: Dermoscopy is a useful tool that helps distinguish lupus miliaris disseminatus faciei (LPDF) from sarcoidosis and tuberculosis. Follicular keratotic plugs (FKP) represent the hallmark of LPDF. Dermoscopic aspect of LPDF changes through the course of the disease. Abstract : Dermoscopy is a useful tool that helps distinguish lupus miliaris disseminatus faciei (LPDF) from sarcoidosis and tuberculosis. Follicular keratotic plugs (FKP) represent the hallmark of LPDF. Dermoscopic aspect of LPDF changes through the course of the disease.